2008
DOI: 10.1128/jcm.01372-08
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Methicillin-Resistant Staphylococcus aureus Molecular Epidemiology after Emergence of Clone USA300 in San Francisco Jail Populations

Abstract: We performed a longitudinal analysis of 502 unique methicillin-resistant Staphylococcus aureus (MRSA) clinical isolates originating from San Francisco jail inmates between 2000 and 2007. Strain USA300, first encountered in 2001, accounted for 82.1% (412/502) of MRSA infections. Non-USA300 MRSA strains were rarely found after 2005 (one isolate in 2006, three in 2007).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
0
16
0
2
Order By: Relevance
“…Many outbreaks have been reported in jails and prisons (136,138,918), and in many urban jails, MRSA has become an endemic pathogen and the predominant etiology of cultured SSTIs (39,215,703,888). There have also been many case reports of detainees and recently released prisoners with MRSA infections (241,299,789,832,835,941,1021).…”
Section: Incarcerated Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many outbreaks have been reported in jails and prisons (136,138,918), and in many urban jails, MRSA has become an endemic pathogen and the predominant etiology of cultured SSTIs (39,215,703,888). There have also been many case reports of detainees and recently released prisoners with MRSA infections (241,299,789,832,835,941,1021).…”
Section: Incarcerated Populationsmentioning
confidence: 99%
“…In the 1990s, several S. aureus genetic backgrounds were responsible for initiating the CA-MRSA epidemic, but by the first years of the 21st century (309,888), one well-characterized genetic background, USA300, emerged as the most prevalent strain in the contiguous 48 states in the United States (403,475,543,702,893,895). Elsewhere in the world, including rural southwestern Alaska (218), other PVL ϩ genetic MRSA backgrounds have predominated (Table 5).…”
Section: Usa300 Strainsmentioning
confidence: 99%
“…It is becoming a common cause of MRSA infection in health care facilities as well (4,5). USA300 is highly virulent, and epidemiologic studies have suggested that it is readily transmitted in jails (6), among athletes (7), and in other settings. It has been associated with skin and soft tissue infections (SSTIs) and invasive, sometimes fatal infections in previously healthy people (8).…”
mentioning
confidence: 99%
“…ommunity-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) infections are among the predominant causes of skin and soft tissue infections (SSTIs) in North America (1), including in detainees in prisons (2-7) and jails (4,(8)(9)(10)(11)(12)(13)(14). Asymptomatic nasal MRSA carriage, a risk factor for clinical infection (15), occurs in 2.7% to 15.8% of U.S. detainees (5,(16)(17)(18), but the nares may not be the primary anatomic site of carriage of CA-MRSA strains (19,20).…”
mentioning
confidence: 99%